EXPLORING LOVE AND LONELINESS IN SZA’S KILL BILL, NOBODY GETS ME, SNOOZE, SATURN, OPEN ARMS, GOOD DAYS - Darmawan, Haikal; Wahyono, Danu (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This study explores how love and loneliness are represented in six selected song lyrics by SZA are Kill Bill, Nobody Gets Me, Snooze, Saturn, Open Arms, and Good Days. The research applies a thematic literary approach to examine how these emotional themes are expressed through poetic language and symbolic signs. This study uses a qualitative method. Figurative language is used to analyze the representation of love, focusing on metaphor, simile, hyperbole, personification, and symbolism. Meanwhile, semiotic theory by Roland Barthes, particularly his concepts of denotation, connotation, and myth is applied to interpret how loneliness is communicated through symbolic signs within the lyrics. The findings reveal that love is expressed with emotional intensity, vulnerability, and deep attachment, while loneliness appears through strong symbolic elements that reflect isolation, emotional pain, and longing. The combination of figurative and semiotic analysis helps to uncover the complex emotional experiences embedded in the lyrics. This study concludes that SZA’s song lyrics provide rich and layered representations of love and loneliness, conveyed through both figurative expressions and symbolic signs.